(untitled) (REMUNOM, 2024)
The present work addresses the impacts of clostridiosis on beef cattle, considering the challenging context that these diseases represent for producers and the industry as a whole. The objective of this study is to analyze the effects of clostridiosis, including its consequences for animal health, herd productivity and food safety. The methodology used consisted of reviewing scientific literature, analyzing epidemiological data and consulting experts in the field of veterinary medicine and animal production. Studies investigating the incidence, risk factors, prevention and control methods, as well as the economic impacts of clostridiosis in beef cattle farming were considered. The results highlight that clostridiosis represents a significant challenge for producers, resulting in high mortality rates, economic losses and food safety concerns. The lack of adequate immunization, inadequate animal management and favorable environmental conditions contribute to the spread of these diseases in herds. It is concluded that the prevention and control of clostridiosis requires an integrated approach that includes management measures, vaccination, health surveillance and collaboration between producers, veterinarians, researchers and regulatory authorities. Only through a multifaceted and proactive strategy will it be possible to effectively reduce the impacts of these diseases and guarantee the sustainability of beef cattle farming.